2013
DOI: 10.1371/journal.pone.0081938
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids Regulate Plant Growth through Distinct Signaling Pathways in Selaginella and Arabidopsis

Abstract: Brassinosteroids (BRs) are growth-promoting steroid hormones that regulate diverse physiological processes in plants. Most BR biosynthetic enzymes belong to the cytochrome P450 (CYP) family. The gene encoding the ultimate step of BR biosynthesis in Arabidopsis likely evolved by gene duplication followed by functional specialization in a dicotyledonous plant-specific manner. To gain insight into the evolution of BRs, we performed a genomic reconstitution of Arabidopsis BR biosynthetic genes in an ancestral vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Consistent with their role in forming structural sterols, such as sitosterol, genes encoding presumptive 24-sterol reductase activity are widely phylogenetically distributed in plants. In agreement with previous studies, we identified similar sequences in both Physcomitrella (Physcomitrella patens) and Selaginella (Mizutani and Ohta, 2010;Cheon et al, 2013;Hamberger and Bak, 2013). Physcomitrella and Selaginella each encode two paralogs that derive from duplication after the divergence of those lineages from each other and the remainder of the taxa (Supplemental Fig.…”
supporting
confidence: 92%
“…Consistent with their role in forming structural sterols, such as sitosterol, genes encoding presumptive 24-sterol reductase activity are widely phylogenetically distributed in plants. In agreement with previous studies, we identified similar sequences in both Physcomitrella (Physcomitrella patens) and Selaginella (Mizutani and Ohta, 2010;Cheon et al, 2013;Hamberger and Bak, 2013). Physcomitrella and Selaginella each encode two paralogs that derive from duplication after the divergence of those lineages from each other and the remainder of the taxa (Supplemental Fig.…”
supporting
confidence: 92%
“…This implies that the BR receptor complex evolved in a common ancestor of lycophytes, gymnosperms, and angiosperms. We found that a total of 67 BR receptors from dicots and monocots can be evolutionarily grouped into three clades represented by AtBRI1/OsBRI1, AtBRL1/OsBRL1, and AtBRL2/OsBRL2 with significant bootstrap support, which is in accordance with a previous study [ 72 ]. Each clade can be divided into two subclades, Ia, Ib, IIa, IIb, IIIa, and IIIb (100% bootstrap support), one subclade from monocots, and the other from dicots ( Figure 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Considering the existence of BRs in single-celled plants [ 64 ], we can not rule out the existence of BR receptor-like proteins in single-celled plants as some receptor kinase proteins might act as BR receptors. Interestingly, Cheon et al [ 72 ] reported that Selaginella lacks a homolog of AtBRI1, but does have downstream proteins such as BIN2, BSU1, and BZR1. This implies that the BR receptor complex evolved in a common ancestor of lycophytes, gymnosperms, and angiosperms.…”
Section: Discussionmentioning
confidence: 99%
“…This cell wall modification apparently evolved as an ancient cell wall consolidation mechanism and is operative in extant members of the charophycean green algae, which are the closest living relatives of land plants (Proseus and Boyer, 2006, Popper et al, 2011, Wolf et al, 2012a, Domozych et al, 2014, Nishiyama et al, 2018. On the other hand, it has been questioned whether BRI1-like brassinosteroid receptors are present in ancestral vascular plants (Cheon et al, 2013), thus RLP44 orthologues could predate some of its interaction partners. It will be interesting to dissect how a protein like RLP44, which modulates the function of distinct RLKs, co-evolved with its interaction partners.…”
Section: Discussionmentioning
confidence: 99%